Features of the innovations in the law enforcement activities of the Gorsky verbal courts of the Terek region in the 90s of the XIX century - Mirbek A. Khagazheev (Кавказология, 2024)
The article focuses on the unique characteristics of the introduction of innovations in the law enforcement activities of the Terek region’s mountain verbal courts in the 90s of the XIX century. The channels and mechanisms for obtaining information by courts on innovations in normative acts and their interpretations from the relevant authorities on the results of law-making activities in the field of judicial proceedings for consideration in their activities are characterized. For this purpose, copies of normative acts of the highest imperial authorities, rules and instructions on conducting individual investigative and judicial actions, orders of the Terek district authorities, copies of reviews from the head of the Terek region and the prosecutor of the Vladikavkaz District Court, etc. were considered. A list of areas in which the SCS received information about their jurisdiction in the late nineteenth century is proposed. The procedure for internally discussing and putting legislative innovations into practice is considered. It is concluded that all of this allowed them to effectively interact with law-making organizations and apply current changes in regulations to their activities.